Casa dentro de casa. A Essência, a Alma e o Refúgio. - Rita Plácido Carneiro (2014)
The house is a complex concept that includes in its definition something that goes far beyond its physical valences. More than an object, the house isn't only characterized by its materialization as a body, for it reaches an incorporeal dimension as if it ascribed a soul to it. «The house» is a term laden with emotional resonance, capable of triggering memories and images, desires and fears, the past, the present and future cravings. A home is not something you can conceive on the spur of the moment, because to acquire its essence it has to be inhabited, and only thus can it fulfill its purpose and the source of its identity. For the house to be acknowledged as such, the immaterial dimension that is intrinsic to its definition cannot be declined, since there is no home without the experiences and memories of its inhabitants. Houses are places of intimate rituals and personalized rhythms which write the history of a family and of the individual's adaptation to the world. The same way as the domestic space acquires its essence by being experienced, it also allows us to emphasize and enhance the senses which allow us to understand what surrounds us and thus become an extension of us. Each house is always different, because there aren't two identical houses in the world, just as no two people are alike. The same house is renewed every day, because we, its older inhabitants, yet different every day, renew ourselves in our Selves constantly.